PENGARUH KOMPETENSI, BUDAYA KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAERAH KABUPATEN LABUHANBATU SELATAN - Ali Brahamsar Nasution; Hasnah Harahap; Indra Arya; Sagiono .; Agus Salim (Manajemen dan Bisnis, 2021)
Problem of this study how influence of competency on performance. How influence of   job culture on performance. How influence of job satisfaction on  performance. How influence competency,   job culture and job satisfaction on   performance. The purpose of this study to determine and analyze the effect of  competency on   performance. Determine and analyze the effect of  job culture on   performance. Determine and analyze the effect of job satisfaction on   performance. Determine and analyze the effect of  competency, job culture and job satisfaction on   performance.  Sample in the study is 34 employees. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate competency variable has a positive and significant effect on performance. Job culture variable has a positive and significant effect on   performance. Job satisfaction variable has a positive and significant effect on performance. Competency, job culture and job satisfaction variable has a positive and significant effect on   performance.